Examining inequities in children's environmental health: results of a survey on the risk perceptions and protective actions of new mothers. Issue 3 (15th March 2016) - Laferriere, K.A.; Crighton, E.J.; Baxter, J.; Lemyre, L.; Masuda, J.R.; Ursitti, F.
Abstract : Young children are more highly exposed and vulnerable to environmental health hazards than adults due to a variety of physiological and behavioural factors. Despite the significant responsibility mothers typically bear in managing their children's health, little is known about how they perceive and negotiate these risks in their day-to-day lives. To better understand mothers' environmental health risk perceptions and associated protective actions across socio-economic and geographic contexts, a telephone survey was conducted among new mothers ( n = 606) recruited through two Public Health Units in Ontario, Canada. Analyses revealed that approximately half of the respondents were moderately or highly concerned about environmental health risks, ranging in nature from household products to outdoor air contaminants. Factors affecting the likelihood of experiencing concern included lower income and lower levels of perceived control. With regard to protective actions, 43% reported taking three or more actions to reduce environmental health risks to their children, with the likelihood of taking action being negatively affected by factors including low income and first language other than English or French, and positively affected by being a first-time parent (primiparous). This study contributes to our understanding of environmental health risk perceptions and associated protective behaviours among new mothers, and has implications for the development of more context-focused risk management and communication strategies.